Nanomedicine: An Emerging Tool in Healing Chronic Wounds and its Opportunities - Kulkarni, Yukta; Chanana, Arsh; Gupta, Pooja; Narayan, Aditya; Shanker, Oma; Patel, Akhilesh; Havelikar, Ujwal; Mahato, Bhabesh; Singh, Dharmendra; Parveen, Sadia; Singh, Ravindra Pal; Chawra, Himmat Singh (Current Indian Science, 2024)
Chronic wounds generally take a lot of time to recover, which becomes a cause of worry for the patient and also makes it difficult to manage them. Chronic wound affects the minds of millions of people worldwide, which results in a high mortality rate. Nanomedicine has emerged as a promising tool in addressing this issue of chronic wounds. Nanomedicine in chronic wound healing holds the potential to revolutionize wound care by offering various personalized treatments and improving patient outcomes. Advanced wound dressings and nanofibresscaffolds promote tissue regeneration, which also accelerates wound closure. Nanomedicine is also able to provoke the various cellular and molecular mechanisms that are involved in the wound microenvironment, showing the anti-inflammatory, antibacterial, and angiogenetic effects. The gene therapy and various inflammation modulations using this emerging tool of nanotechnology show promising results in managing the various chronic wounds. Nanomedicine offers innovative approaches to address these challenges. Nanomedicine also plays a crucial role in tissue engineering, which can also be used for chronic wound treatment. Nanotechnology has enabled the various development of advanced wound dressings and has improved various properties. Nanomedicine also uses antimicrobial nanomaterials, such as silver nanoparticles, to combat the various infections in chronic wounds. The main aim of the review is to provide a concise overview of nanomedicine as a recent tool in healing chronic wounds and also its various opportunities for curing chronic wounds.
Keywords: Nanomedicine